Identifying the Most Critical Factors to Business Intelligence Implementation Success in the Public Sector Organizations - Magaireh, Asma Ibrahim; Sulaiman, Hidayah; Ali, Nor’ashikin (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
The BI is a new trend in public sector organizations that requires investigating the critical success factors (CSFs) which would provide a sound guidelines for determining the criteria to be considered during BI implementation. However, there is no sufficient empirical evidences that provide better understanding of the CSFs for the BI implementation in public sector organizations. This paper aims to identify the CSFs for BI system in the context of public sector organizations. This study adopts a mixed method approach using survey research method and qualitative interview using Jordanian public sector organization case. The findings of this research revealed that top management support, clear vision and strategic planning, team skills, user participation, organizational structure, user access and development technology are the most critical factors to BI implementation success in the public sector organizations. The findings of this study could assist the practitioners in the public sector organizations in planning, managing and implementing their BI projects properly by focusing on those CSFs of BI systems that provide them a better understanding to address issues and concerns related to BI implementation.